The effect of a postmodern career life story intervention on disadvantaged grade 12 learners - Tinsley-Myerscough, Sarah; Seabi, Joseph (South African Journal of Higher Education, 2016)
This study sought to investigate the effectiveness of postmodern qualitative narrative counselling in the South African context, where traditional western approaches have been less successful, by exploring the effects of a postmodern career life story intervention on a sample of eight disadvantaged grade 12 learners. A qualitative research design using pre and post intervention interviews was used to explore whether the participants reevaluated or reinterpreted their responses to the interview questions in light of the intervention. The results of the study indicated that the participants experienced increased self-understanding, self-esteem, initiative and hope, optimism and empowerment through the intervention. The participants appreciated the time and space to be able to reflect on their lives. It appears as if all the various components of the life story intervention had a powerful impact on the participants. Writing life stories and using art materials appeared to be a method that was effective with disadvantaged grade 12 learners.